Stability analysis of pedestrian-induced large lateral vibration on a footbridge. Issue 3 (4th March 2021) - Jia, Buyu; Yu, Xiaolin; Yan, Quansheng; Yang, Zheng; Chen, Yuxuan
Abstract: Stability analysis for pedestrian-induced vibration on footbridges is a complicated and multidisciplinary problem, which includes a series of complex mechanics, such as pedestrian–bridge interaction, vibration instability, and excitation randomness. Thus far, an effective method of dealing with such problem remains lacking. In this study, a novel nonlinear stochastic vibration model is proposed by fitting the laboratory data of Ingólfsson et al., and the analytical solution is obtained by using the stochastic average method. Then, the steady and stability solutions of the lateral vibration of the Millennium Bridge are analysed in detail. Based on the analysis results, the influence of the number of pedestrians, the frequency tuning, and the randomness of excitation on the vibrational stability of footbridges are revealed. The method proposed in this study can also be applied to other nonlinear vibration models, and it provides a reference for future nonlinear stochastic analysis of pedestrian-induced vibration on footbridges.